The Role of Competition Law in Regulating Corporate Conduct, Protecting Consumers and Enhancing Economic Efficiency - Muhammad Bahrudin; Anang Prabowo; Agus Eko Sujianto (Economics and Business Journal (ECBIS), 2026)
This study aims to examine the role of competition law in regulating corporate conduct, protecting consumers, and enhancing economic efficiency in contemporary market economies. Amid increasing market concentration, digital platform dominance, and the emergence of data-driven business models, competition law has become an essential regulatory instrument for ensuring fair competition, safeguarding consumer interests, and promoting sustainable economic development. This study employs a Systematic Literature Review (SLR) based on the PRISMA 2020 framework. Relevant literature was systematically collected from six major academic databases, namely Scopus, Web of Science, ScienceDirect, SpringerLink, Emerald Insight, and Taylor & Francis Online. The review process included identification, screening, eligibility assessment, and inclusion stages. A total of 78 peer-reviewed articles published between 2015 and 2025 were selected and analyzed using thematic synthesis techniques. The findings reveal that competition law performs four interconnected functions. First, it serves as a regulatory mechanism that shapes corporate behavior and prevents anticompetitive practices, including monopolization, cartel agreements, price-fixing, and abuse of dominant positions. Second, competition law enhances consumer welfare by promoting competitive prices, product quality, innovation, and consumer choice. Third, effective competition policy contributes to allocative, productive, and dynamic efficiency, thereby supporting long-term economic growth. Fourth, digital markets introduce new challenges associated with data concentration, platform dominance, network effects, and algorithmic pricing, requiring adaptive regulatory frameworks and strengthened institutional capacity.This study contributes to the literature by integrating Economic Efficiency Theory, Consumer Welfare Theory, Competition Policy Theory, and Regulatory Governance Theory into a comprehensive analytical framework that explains the relationship between competition law, corporate conduct regulation, consumer protection, and economic efficiency.The findings provide policy recommendations for competition authorities and governments, particularly in developing economies, regarding digital competition governance, institutional strengthening, cross-border enforcement cooperation, and data-driven market regulation.Unlike previous studies that focus on isolated dimensions of competition law, this research offers a holistic synthesis of legal, economic, consumer welfare, and governance perspectives. It further highlights how competition law can address emerging challenges in the digital economy while simultaneously promoting consumer protection and economic efficiency.